Peer Assessment in German Writing Essay for 11th Graders of Language Class SMA Islam Kepanjen Malang - Maula Zahra; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This study aims to describe the students' writing errors that often appear in writing essays and to describe results of the peer assessments. This research was conducted offline to 13 students of class XI Language of SMA Islam Kepanjen Malang. To collect data, a test technique was used using instrument, namely the Family theme writing test. Then, the essays were assessed by peers based on completeness of content, communicative form, and grammar. To answer the purpose of describing students' writing errors, the study shows grammatical errors often appear. In the aspect of completeness of content, most of content related to 'hobby' were not written by students. Communicative form errors are made, because they often do not use connecting words between sentences. Related to the second purpose, in peer assessment students are fully involved in identifying errors, correcting, and providing feedback. Grammatical errors also occupy the highest number of errors.